Percutaneous Endoscopic Necrosectomy (PEN) Combined with Percutaneous Catheter Drainage (PCD) and Irrigation for the Treatment of Clinically Relevant Pancreatic Fistula after Pancreatoduodenectomy - Jian Lin; Biqing Ni; Guozhong Liu (Journal of Investigative Surgery, 2020)
Purpose: This study aimed to evaluate the efficacy of percutaneous endoscopic necrosectomy (PEN) combined with percutaneous catheter drainage (PCD) and irrigation versus PCD for the treatment of clinically relevant postoperative pancreatic fistula (CR-POPF) after pancreatoduodenectomy (PD). Materials and Methods: A total of 34 consecutive patients who suffered from CR-POPF after PD were enrolled in this retrospective cohort study. 12 patients received PEN combined with PCD and irrigation, and 22 patients received PCD. The complications and outcomes of the treatments were compared. Results: No patients suffered from severe PCD- or PEN-related complications. Compared with those treated with PCD, the patients treated with PEN combined with PCD and irrigation had a lower incidence of postoperative delayed severe intraabdominal hemorrhage (31.8% vs. 0%; p = 0.04). During the follow-up period, no patients in either group suffered from collection recurrence or external pancreatic fistula requiring surgical intervention. Conclusions: PEN combined with PCD and irrigation was safe and effective for reducing postoperative delayed severe intraabdominal hemorrhage in patients with CR-POPF after PD.